Cardiac muscle remodeling after therapeutic hypothermia and allogeneic mesenchymal stromal cells in a model of myocardial infarction - Чиж, М.О.; Manchenko, A.O.; Troﬁmova, A.V.; Belochkina, I.V. (Problems of Cryobiology and Cryomedicine, 30(3): 284., 2020)
Cardiac muscle remodeling after therapeutic hypothermia and allogeneic mesenchymal stromal cells in a model of myocardial infarction
Ремоделювання серцевого м’язу після застосування терапевтичної гіпотермії і алогених мезенхімальних стромальних клітин на моделі інфаркту міокарда
Chizh М.O., Manchenko A.O., Troﬁmova A.V., Belochkina I.V. (2020) Cardiac muscle remodeling after therapeutic hypothermia and allogeneic mesenchymal stromal cells in a model of myocardial infarction. Problems of Cryobiology and Cryomedicine, 30(3): 284.
Keywords: remodeling; cardiac muscle; hypothermia; infarction model; stromal cells